2021
DOI: 10.1680/jmaen.2020.17
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on fatigue damage calibration factors in offshore structures

Abstract: Fatigue damage in marine structures is generally assessed by means of stress−number of cycles (S−N) curves. These curves are obtained from many experimental tests on structural components. Fracture mechanics (FM), using the crack propagation method is also a practical technique. In this approach, fatigue damage is estimated based on crack propagation from an initial crack size through the surface and depth of structural members. In this paper, S−N curves based on FM were compared with S−N curves obtained follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Figs. [7][8][9][10][11][12] show the comparison between the stresses obtained from the Efthymiou's formulations proposed by DNVGL with the stresses obtained from the numerical simulations of the different meshes performed in this study. It is observed great conformity and compatibility between the numerical and the Efthymiou solutions in most points of the braces under analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figs. [7][8][9][10][11][12] show the comparison between the stresses obtained from the Efthymiou's formulations proposed by DNVGL with the stresses obtained from the numerical simulations of the different meshes performed in this study. It is observed great conformity and compatibility between the numerical and the Efthymiou solutions in most points of the braces under analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Codes and recommendations such as those from the International Institute of Welding -IIW [10] and DNVGL [11] provide global fatigue damage approaches, based on S-N curves, to be applied to welded joints, the latter being specific for offshore structures. Shabakhty et al [12] presented a discussion on the fatigue resistance modelling based on the fracture mechanics (FM) based-approach, where a comparison between the obtained S-N curves following two standards, DNVGL-RP-C203 [11] and API-RP2A-WSD [13], was done. These authors concluded that to obtain better fitting with the S-N curves, calibration factors are needed, and, therefore, these factors have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Hot-spot is defined as the region in the joint where fatigue cracks are more susceptible to appear due to cyclic loading, meaning that hot-spot stress is the value of the stress in the surface of the hot-spot. Radaj [58] demonstrated that the hotspot stress corresponds to the sum of the membrane and bending stresses at the weld toe, which can be determined through extrapolation [57,59]. According to DNVGL recommendations, notch stresses must be considered in special cases in which is hard to evaluate with assurance the fatigue strength using other methods.…”
Section: Analysis and Stress Concentration Factorsmentioning
confidence: 99%